Ethiopia: Joint sector review assessment: Advancing mutual accountability through comprehensive, inclusive, and technically robust review and dialogue - Ministry of Agriculture, Ethiopia (Government of Ethiopia, Ministry of Agriculture, 2014)
Ethiopia’s key development objectives are poverty eradication and food security at the household level, with agriculture playing an important role in the achievement of both of these objectives. The major policy framework for doing so is the Agricultural Development-Led Industrialization (ADLI) strategy, which has been the central pillar of Ethiopia’s development vision since the 1990s. Agricultural sector growth in the short and medium terms is envisaged as the driver for long-term industrialization and the structural transformation of Ethiopia’s economy. Ethiopia indigenized the Comprehensive Africa Agricultural Development Programme (CAADP) by signing a CAADP Compact in August 2009 and developing the Agricultural Sector Policy and Investment Framework (PIF), which is the country’s National Agricultural Investment Plan. PIF is a 10-year plan that targets 8 percent annual growth in agricultural gross domestic product. It prioritizes agricultural subsectors for investment, estimates financing needs, and provides an implementation roadmap. To further support CAADP implementation, Ethiopia signed the G8 [Group of Eight] Cooperation Framework to support the New Alliance for Food Security and Nutrition in 2012. The G8 Cooperation Framework aims to catalyze private-sector investment in seed development, multiplication, and distribution. It also seeks to put mechanisms in place to improve the ability of Ethiopia’s private sector to access markets, land, and credit.